Weak solutions to a model with elasticity energy for electrochemically induced phase transitions in Lithium-Ion batteries. (June 2021) - Cheng, Fang; Hu, Ye; Zhao, Lixian
Abstract: Using olivine LiFePO4 as a model system, we study the existence of global solutions to a phase-field model with elasticity energy for Lithium-Ion batteries, which consists of a linear elasticity sub-system and nonlinear evolution equations for the order parameter and the lithium concentration. This model can be described the evolving microstructure for electrochemically induced phase transitions in electrochemical storage. Our numerical experiments are carried out to simulate the evolutions of lithium concentration and of phase interfaces for the model.